If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12y+15=6y+21
We move all terms to the left:
12y+15-(6y+21)=0
We get rid of parentheses
12y-6y-21+15=0
We add all the numbers together, and all the variables
6y-6=0
We move all terms containing y to the left, all other terms to the right
6y=6
y=6/6
y=1
| x-12+4x-2=4x-14 | | 19=w-34 | | -10(9x-4)=-6x | | 4x-5=6x+30 | | 28=k/9+26 | | 3/7w=114/7 | | 5=-x/19-2 | | x+34=x+64+90 | | -2(2x+1)=-5x+3+x | | 5u-6=4u | | 7(5-2x)=84x | | 2/9(x+18)=10 | | 7q-9=89 | | 2t-6=3t-40 | | 8=-4+p | | -6x=-10(9x-4) | | 13y+14=4y+77 | | 45=11-2x | | -6n+22=-4n+12 | | 9x+36=3(x+20) | | z+60=8z+46 | | 0.06x+0.03=7.2 | | 4(5x+10)=0 | | 4s+12=20 | | 8x-11=-11 | | 5(x-1)-2×=x-19 | | u+26=2u+14 | | 9(v-95=36 | | 12(35-5x)=180 | | {2/3}x+5=1 | | 46=11-2x | | 8x+83=14x+59 |